The effect of individually adjusted workstations on upper quadrant posture and muscle activity in school children - Straker, Leon; Briggs, Andrew; Greig, A. (IOS Press, 2002)
Evidence suggests there is increasing use of computers by children and poor workstation designs for children. This laboratory study investigated the effect of adjusting computer display height and desk height on upper quadrant posture and muscle activity. Thirty three children aged 4–17 years worked on a desktop computer at a standard school workstation and at a workstation adjusted to the individual, typically consisting of a lower display and desk height. The adjustments resulted in increased head tilt, neck flexion, gaze angle, cervical erector spinae activity and a trend for lower right upper trapezius activity. The recent evidence that suggests more head and neck flexion is not necessarily worse is discussed and normative values for children’s head tilt and neck flexion presented. The role of forearm support in decreasing trapezius activity is also discussed.